Analisis Analisis Strategi Marketing Syariah Dalam Produk Pembiayaan Konsumtif Pada BPRS BMI Sepanjang: Analysis of Sharia Marketing Strategy in Consumer Financing Products at BPRS BMI Sepanjang - Rahmawati, Aisha; Saqofa Nabilah Aini; Alannawa, Sonia Rosta; Afifah, Istiqomatul (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2024)
This research aims to analyze the sharia marketing strategy of segmentation, targeting and positioning in consumer financing products at BPRS BMI Panjang Branch. This type of research is descriptive qualitative. The data collection methods used were observation, interviews and documentation. The results of this research indicate that the segmentation strategy used in consumer financing products by BPRS BMI Panjang Branch is demographic and geographic segmentation. The targeting strategy used in consumer financing products is using a concentrated market. And also the positioning strategy applied in financing products, namely product positioning based on: (1) attributes, namely being known for its fast process and easy installments; (2) prices, price provisions or installments that are low; and (3) the use of slogans is an effort to position financing products.